Interpretation of river water quality using environmetric techniques and statistical process control performances for selected river basins in Peninsular Malaysia - Samsudin, Mohd Saiful (2014)
The river basin pollution becomes a serious issue in Peninsular Malaysia. This research is to clarify river water quality using environmetric techniques (PCA, MLR and HACA) and statistical process control (control chart and capability indices) performances consist of three river basins (North-Middle-South) in Peninsular Malaysia. Commonly, lack of knowledge of analysis and modeling for river pollution are unable to encounter either present or future river pollution loading in Malaysia. Besides, total water quality management by using statistical approaches are needed for a sustainable environment. Nevertheless, quality engineering tools are not often applied in river pollution problems for a sustainable environment. The abundant water quality data monitoring are required to utilize for exact identification and distribution of pollution for more effective and optimized sampling strategy. The objectives of this research are to identify the types of pollution sources in each of the river basins, to determine the most significant parameters of each river basin which contribute to river pollution loading and to discover the potential contamination of pollutants and perform the process capability of water quality. In this study, secondary data from monitoring stations under the river water quality monitoring program by the Department of Environment (DOE) from 2003 to 2007 were packed into consideration to extract the spatial-temporal information on Perlis River, Klang River and Johor River. From this study, the deviations of the types of pollution sources and dissimilar of significant possible pollution sources can be sanctioned. In Perlis River Basin, the results show BOD and COD as the principal parameters which indicate as the quantity of the agricultural pollution. For Klang River Basin, NH3-N has been unveiled as the main parameters which indicate from anthropogenic activities. Johor River Basin has revealed NH3-N and PO4 as the main parameter as the main pollutants that give highest contribution towards the river and it is believe from land alterations towards oil palm plantation. However, SPC indicates the level of all significance parameters concentration for each basin shown the risk of unacceptable water pollution level according to WQI. This is because of a dissimilar type of human activities and area development surrounding the study areas. This study shows the important of statistical analysis and modeling for river water quality management to save time consuming and help to save money in managing river water quality analysis.